2017
DOI: 10.1016/j.drugpo.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Using database linkages to monitor the continuum of care for hepatitis C virus among syringe exchange clients: Experience from a pilot intervention

Abstract: Background Because many people who inject drugs (PWID) are at high risk of hepatitis C virus (HCV) and have poor access to medical care, many HCV-infected PWID remain undiagnosed and unaccounted for in surveillance systems. Syringe exchange programs (SEPs) are an under-utilized resource for collecting information missing from surveillance systems. Partnerships with public health agencies represent a potentially innovative approach to studying the HCV epidemic for PWID. The goal of this study was to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Despite HCV therapeutic advances, challenges remain for HCV screening and linkage to care. Investigations conducted around the US have found that a low proportion of individuals who test positive for HCV are linked to care and few receive treatment (Bourgi et al 2016 ; Hochstatter et al 2017 ; Viner et al 2015 ). Two large population-level studies of HCV in the United States conducted by the CDC, the Chronic Hepatitis Cohort Study (CHeCS) and the National Health and Nutrition Examination Survey (NHANES), demonstrate that 32–38% of those who test positive for HCV antibodies receive follow-up HCV care and 7–11% are treated (Moorman et al 2013 ; Spradling et al 2012 ; Denniston et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite HCV therapeutic advances, challenges remain for HCV screening and linkage to care. Investigations conducted around the US have found that a low proportion of individuals who test positive for HCV are linked to care and few receive treatment (Bourgi et al 2016 ; Hochstatter et al 2017 ; Viner et al 2015 ). Two large population-level studies of HCV in the United States conducted by the CDC, the Chronic Hepatitis Cohort Study (CHeCS) and the National Health and Nutrition Examination Survey (NHANES), demonstrate that 32–38% of those who test positive for HCV antibodies receive follow-up HCV care and 7–11% are treated (Moorman et al 2013 ; Spradling et al 2012 ; Denniston et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Routine and/or opt-out testing programs upon intake to prison, coupled with automatic laboratory reporting processes, provide the opportunity to collect information on the HCV epidemic among incarcerated populations. These processes ensure HCV-infected individuals cycling through correctional facilities are accounted for in public health surveillance systems, and thus provide useful tools for evaluating the HCV care continuum for individuals as they transition in and out of the criminal-justice system (Hochstatter et al 2017 ). The overall goal of this study was to characterize the receipt of HCV care and treatment services for a cohort of HCV-infected adults identified in a single state prison system.…”
Section: Introductionmentioning
confidence: 99%
“…However, a unified approach to defining the HCV CoC stages is lacking. Consequently, findings are being reported in highly diverse ways [9][10][11][12][13][14]. A similar situation in the HIV field limits the comparative value of HIV CoCs and makes it difficult to aggregate data for accurate assessments of progress at the regional and global levels [15].…”
mentioning
confidence: 99%
“…At the time of the baseline assessment, 93% of HCV RNA–positive individuals reported they had seen a medical provider for HCV, a level substantially higher than what had been reported in prior studies [26,53,54]. Because the survey questions did not specifically ask whether participants saw a provider specifically to discuss starting HCV treatment, our study may overestimate true linkage to HCV care.…”
Section: Discussionmentioning
confidence: 73%